EFFECT OF TEAM WORK AND FINANCIAL COMPENSATION ON EMPLOYEE PERFORMANCE AT CV. BIN HAM MANDAILING NATAL - Nurfatimah; Ainun Mardhiyah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study aims to determine and analyze how the influence of team work and financial compensation on employee performance at CV. Bin Ham Mandailing Natal. This study uses the associative method with a quantitative approach. The sample in this study were all employees of CV. Bin Ham Mandailing Natal as many as 35 respondents. The data analysis method used is validity and reliability test, classical assumption test, multiple linear regression analysis test, hypothesis test through T test and F test, and coefficient of determination test. Based on the results of the study, it was discovered that the Team Work had a partial effect on employee performance, this was evidenced by the value of Tstatistic (3,659) > Ttable (2,036). While the financial compensation variable has a partial effect on employee performance, this is evidenced by the value of Tstatistic (3,464) > Ttable (2,036). Based on simultaneous testing, the employee performance variable has a simultaneous effect on Team Work and financial compensation with the Fstatistic 19,352 > Ftable (3,294), and the R value is 0,740 and the Adjusted R Square in this study is 0,547 while the remaining 45,3% influenced by other factors beyond the study.